Boundeness of Cauchy singular integular in Morrey space with variable (t - متوج , كوثر; محمد علي; حسن خليفة (Latakia University Journal -Basic Sciences Series, 2023)
Regarded Cauchy singular integral of the important mathematical tools used to answers to many of mathematical problems , so in this research we studied some features singular Cauchy's integral for functions belong to wide classes of functions on a famous curves families.It is one of the most important properties that are studied on the singular Cauchy's integral is its boundness ,existence,and affiliation ,All of these properties are studied when belonging to the function f to a space ,And through this study we have obtained some results about singular Cauchy's integral and its boundness in Generalized Morrey space with variable (t).